PENGARUH DEMONSTRASI PIJAT BAYI TERHADAP MINAT IBU UNTUKMELAKUKAN PIJAT BAYI SECARA MANDIRI - Nugroho, Christianto (Jurnal AKP, 2013)
Massage is the art of infant health care and treatment which is known from the beginning man was created in the world and has been practiced since centuries ago hereditary years by traditional birth attendants. There are still many women who do not know about infant massage, especially the benefits and how to massage baby the right that can be done independently by mothers due to lack of interest. Enthusiasm is the initial impetus that affect attitudes and behavior of mothers in infant massage independently. To increase interest in the mother can be done with counseling by using the method of demonstration. The purpose of this study was to determine the influence of infant massage demonstration against the interest the mother to perform infant massage on their own. Design research is experimental quassy. The population studied were all mothers who had infants aged 0-12 months in the Village posyandu Kencong Surround Kediri subdistrict number of 39 respondents with engineering use samplig random sample of 35 respondents obtained. Data collection using koesioner in interest before and after the demonstration. The results of data collection were analyzed by Wilcoxon matched pairs test.Based on the results of research conducted it appears that an increase in the number of respondents who have high interest. Statistical test results with values obtained using Wilcoxon Test Z=-4,426 and p-value = 0.00 is less than Î± = 0.05, so that H0 rejected and H1 accepted. This indicates there is a demonstration effect on infant massage to the interest Mother Infant Massage To Perform Self In Posyandu Village District Kencong Surround Kediri Year 2011. Based on the research for the health institutions are expected gets to increase effort any other besides counselling to increase motherÂ  does to massage independent massage baby Â Keywords: Demonstration, Infant Massage, Interest.